Screening and characterization of potential probiotic and starter bacteria for plant fermentations - Vera Pingitore, Esteban (2016)
Probiotics are mostly consumed as fermented or fortified food products in Europe. There are two important factors in the selection of probiotic candidates regarding the potential health benefit; their viability and number when consumed, and their survival and persistence in the gastrointestinal tracts. This study focusses on the selection of potential probiotics to be used as starter culture in plant-based fermented foods. Lactic acid bacteria isolated from quinoa and amaranth were tested in vitro for their sensitivity to antibiotics, tolerance to gastrointestinal stress factors and adhesion to gut epithelial cells. Only five strains had suitable antibiotic profile to be used as probiotics and all of them were tolerant to lysozyme, bile salts, and had similar adhesion capacity. Lactobacillus plantarum Q823, administered as starter culture in a fermented quinoa drink, was selected for the human in vivo tests, because of its best in vitro tolerance to low pH. This strain was able to survive and persist at detectable levels (5–7 Log10 CFU/g feces) in the gastrointestinal tracts for at least seven days after the end of administration. Thus, L. plantarum Q823 has been identified as a suitable starter and a potential probiotic in fermented quinoa-based products.